2005
DOI: 10.3758/bf03195322
|View full text |Cite
|
Sign up to set email alerts
|

Gaze behavior in analytical and holistic face processing

Abstract: Humans are experts at recognizing faces. We identify faces quickly and exactly without any effort. Small wonder, then, that extensive research has been carried out to understand the stages of information processing that underlie face-recognition performance. The two relevant stages of information processing are perceptual encoding and information processing. In the area of face processing, most studies have focused on the latter and have shown that people often use the configural processing mode-processing the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
54
2

Year Published

2006
2006
2019
2019

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 63 publications
(59 citation statements)
references
References 43 publications
(53 reference statements)
3
54
2
Order By: Relevance
“…Since the hereditary prosopagnosics of the present study also included information on the external parts of the faces in their gaze behaviour this fact can be understood as a parallel between children's and hereditary prosopagnosics' way to process faces. Another parallel refers to the observation that children's gaze behaviour is less focused than that of adults when they were viewing faces (Schwarzer, Huber & Dü mmler, 2005). Thus, there seem to be slight parallels between children's and hereditary prosopagnosics' way to examine a face visually.…”
Section: Discussionmentioning
confidence: 95%
“…Since the hereditary prosopagnosics of the present study also included information on the external parts of the faces in their gaze behaviour this fact can be understood as a parallel between children's and hereditary prosopagnosics' way to process faces. Another parallel refers to the observation that children's gaze behaviour is less focused than that of adults when they were viewing faces (Schwarzer, Huber & Dü mmler, 2005). Thus, there seem to be slight parallels between children's and hereditary prosopagnosics' way to examine a face visually.…”
Section: Discussionmentioning
confidence: 95%
“…We are not the first to assume that the difference between a same-different and a 2AFC task using the same stimuli is a more holistic processing of the face stimuli in the latter: Beale and Keil (1995) developed their "better-likeness" task (i.e., participants must judge which of two images is the better likeness of a particular person) specifically to bias observers, in contrast with discrimination tasks, to more holistic processing. Furthermore, in a study of face perception in children and adults, Schwarzer, Huber, and Dümmler (2005) found that participants' RTs were significantly faster when a holistic strategy was used, rather than a feature-based strategy for the same task, indicating that the processing of facial features is time consuming. Faster RTs were also found in the feminine task of our present experiment than were found in the sex task using the same face stimuli.…”
Section: Gaze Behaviormentioning
confidence: 99%
“…Furthermore, participants encouraged to engage in analytical processing tend to fixate on each feature individually, whereas participants engaging in holistic processing tend to fixated in a central position between the eyes (Schwarzer et al, 2005).…”
mentioning
confidence: 99%
“…That is, that the ideal fixation point for accurate encoding is weighted according to the diagnostic value of the nearby features. The region that provides the most amount of holistic information is between the eyes (e.g., Schwarzer et al, 2005) because the eyes are of more diagnostic value (e.g., Haig, 1986a, b). 7 By implication, the assumption is configural processing is at least related to holistic processing.…”
mentioning
confidence: 99%